Prevalence and correlates of low self-reported physical health status among prisoners in New South Wales, Australia. Issue 2 (10th June 2019) - Ross, Joanne; Field, Courtney; Kaye, Sharlene; Bowman, Julia
Abstract : Purpose: The purpose of this paper is to examine the prevalence and predictors of low self-reported physical health status among NSW prison inmates. Design/methodology/approach: Cross-sectional random sample of 1, 098 adult male and female prisoners, interviewed as part of the 2015 Justice Health and Forensic Mental Health Network Patient Health Survey. Findings: Almost a quarter of participants had "low self-reported physical health status". Independent predictors of "low health status" were having been in out of home care before the age of 16 years, being illiterate, smoking 20 or more cigarettes a day, not eating more than one serve of fruit a day, not being physically active in the 12 months before incarceration, higher body mass index score and low self-reported mental health status. Many of these predictors are modifiable risk factors for chronic disease, which could be targeted during incarceration. Originality/value: This paper demonstrates the utility of a using a single item measure of self-reported physical health status among Australian prisoners, and helps to characterise those prisoners in greatest need of intervention for issues relating to their health.